Penerapan Metode Waterfall Dalam Membangun Aplikasi Kursus Programming Berbasis Web - Supriatiningsih, Supriatiningsih; Mulyanto, Joko Dwi (Informatics and Computer Engineering Journal, 2025)
Currently, the world of work requires skilled labor with work-ready skills. One of the skills needed in the world of work is computer skills. Course education institutions can be used as an alternative to learning the skills needed by the world of work. Therefore, many course education institutions (LPK) have sprung up that organize work-ready education to meet the needs of the world of work. Kurus programming is a course education institution that focuses on programming languages, namely web programming, java, and c++ which aims to help students to make projects or assignments. The coding course application system at skinny programming is a website-based system in the IT field, it is hoped that this system can help course management and facilitate student data management, scheduling and management of payment funds from students. With this system, it can facilitate students to register, select tutors, select the desired course class, and select the main material. The obstacles that researchers find in thin programming include registration, both students and tutors are still written by hand, making schedules and payment systems are also still done by recording all existing transactions using handwriting and in the book in writing, because using handwritten data is prone to loss such as being exposed to water or torn so that researchers make this system so that data is safe and easy to find again, difficulty in finding tutors that suit your needs and promotions that are not yet widespread. The method used is the Waterfall method which is divided into several stages: Software Requirements Analysis, Design, Program Code Generation, Testing and maintenance. For this reason, researchers try to create a web-based coding course information system in the hope that it can provide convenience for students or students in doing assignments.